Determinant of acquisition of financial institution - Johan, Suwinto (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2019)
This study is aimed to investigate the determinants of finance companies’ acquisition. During the last 15 years, there were more than 30 mergers and acquisition deals happened in the finance company industry. We have analyzed six micro financial ratios which are productivity ratio, profitability ratio, equity capitalization, leverage ratio, asset composition ratio, and firm size. The dependent variables are dummy variables of acquisition. The financial ratios are OER (operating efficiency ratio), ROE (return on equity), leverage, asset allocation ratio, equity size and firm size. The samples are the 90 finance companies who issued financial report from 2001-2015. Data were analyzed using panel data regression. The results of the study found that only company size had a significant effect on finance companies acquisition